LOW-COST DRONE INSPECTION AND DESTRUCTION - Davis, William, author; Heyliger, Paul, advisor; McGilvray, Kirk, committee member; Guo, Yanlin, committee member; Fankell, Doug, committee member (Colorado State University. Libraries, 2026)
This research investigates the development and validation of low-cost systems for structural anal-ysis and drone defense. Two unmanned aircraft systems (UAS) were created to capture high- resolution imagery for photogrammetry-based three-dimensional modeling of infrastructure. The resulting models were processed into a format suitable for finite element analysis (FEA) using commercially available software. Multiple structures including railroads, bridges, buildings, and concrete surfaces, were evaluated to assess accuracy and practical usability of the modeling ap- proach. Quantitative comparisons between physical measurements and digital models demonstrate that low-cost photogrammetry can produce results suitable for structural and concrete degradation analysis, though computational processing time remains significant. A large-scale air-driven Shock Tube was designed and fabricated to generate repeatable impulse pressure waves without the use of regulated explosives. Experimental results show that the system produces pressure profiles comparable in magnitude to the detonation of an explosive charge. In addition, a vortex cannon system was developed to investigate the formation of high-energy vortex rings for drone defense and avalanche control applications.
Keywords: Drone; Structural Analysis; Vortex Ring Cannon; Shock Tube; C-UAS; UAS